THE INFLUENCE OF ARABIC-MALAY LANGUAGE ON THE FORMATION OF RELIGIOUS TERMS IN MODERN INDONESIAN - Salmiyanti; Sri Mawaddah (CV Naskah Aceh, 2025)
Indonesian as a national language did not emerge in a vacuum. It is the product of a long historical process involving various linguistic and cultural influences, among which Arabic and Malay stand out prominently. This article investigates the impact of the Arabic-Malay linguistic nexus on the formation of religious terminology in modern Indonesian. Based on the premise that most Islamic religious terms used in contemporary Indonesian are derived from a blend of Arabic—the language of Islam—and Malay—the primary medium of Islamic dissemination in the archipelago—this study adopts a descriptive qualitative and historical-linguistic approach. It traces the origins, phonetic adaptation, morphological changes, and semantic evolution of religious vocabulary. The findings reveal that Arabic-Malay influence extends beyond lexical aspects, shaping the sociocultural function of the Indonesian language in religious discourse. This paper affirms that the Arabic-Malay linguistic legacy has significantly contributed to the legitimacy and authority of Indonesian in articulating Islamic teachings.